Effect Of Some Bean Cultivars Phaseolus Vulgaris L. In The Greenhouse on Anatomical Characteristics - Abrar A. Naser; Wathik A. Aziz; Ammar H. Saeed; Abrar A. Naser; Wathik A. Aziz (Jurnal MIPA dan Pembelajarannya, 2026)
The experiment was taken place at the Horticulture and Landscape Engineering Department, Tikrit University, Greenhouse Unit during the period of 2022–2023 growing season to study the effect of four bean cultivars on anatomical traits. The results revealed significant differences among the cultivars. The results showed Gia Bean cultivar outperformed the others in terms of cuticle thickness on both the upper and lower leaf surfaces, as well as epidermal cell dimensions on the upper surface. Meanwhile, the Seychelles cultivar showed greater values  in epidermal cell thickness (upper and lower surfaces), mesophyll tissue thickness, stomatal dimensions on both surfaces, and lower surface epidermal cell dimensions, in addition to having the highest stomatal frequency on the lower surface and the Ferrari cultivar was differentiated by the highest stomatal frequency on the upper surface.